Assessment of Farmer-Led Irrigation Development in Rwanda - Nzeyimana, Innocent (World Bank, Washington, DC, 2021)
Irrigation development in Rwanda is typically not demand-driven. Existing irrigation developments have mostly resulted from government-led initiatives and donor support with the aim of achieving food security. A few irrigation projects have also been initiated by private commercial farmers and smallholder farmers with use of small-scale irrigation technology (SSIT). Farmer-led irrigation development (FLID) is defined as a process by which small-scale farmers or commercial farmers drive the establishment, improvement, and/or expansion of irrigated agriculture, often in interaction with external actors. It typically involves entrepreneurial investments by farmers either alone or in groups. For the FLID supply chain to be effective and efficient, several key private and public sector participants are involved. Districts, sectors, and offices are key stakeholders that deliver agriculture extension and advisory services and serve as focal points representing the needs of local communities and coordinating multisector responses. Regarding FLID financing, the government has attempted to reform policies and increase access by smallholder farmers to financial services. As a result, different commercial banks both public and private, MFIs, and other financial service providers continue to expand their financial services to poor rural communities, especially smallholder farmers.